2019
DOI: 10.21093/di.v19i1.1506
|View full text |Cite
|
Sign up to set email alerts
|

The Current Issues of Indonesian EFL Students’ Writing Skills: Ability, Problem, and Reason in Writing Comparison and Contrast Essay

Abstract: The aim of this study is to investigate issues of Indonesian EFL students’ writing skills, covering ability, problem and reason why they got problems in writing comparison and contrast essay. The convergent parallel of mixed methods was used to explore these issues by involving 52 EFL students of IAIN Samarinda who enrolled the academic essay writing course. The three research instruments; essay writing test, open-ended questionnaire and interview were used in the data collection. The findings of this study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
123
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 15 publications
15
123
1
6
Order By: Relevance
“…The findings of this research showed that 50% respondents acquired fair score, and 17% was in poor qualification for their English writing. This finding was different from a study conducted by Toba, Noor, & Sanu (2019) who found that the English writing ability of undergraduate students can be considered as good. In addition, the results of this study was also not in line with Husin & Nurbayani's study (2017) who explained that the average score of thesis written in English by university students were relatively good quality.…”
Section: The Factors Inhibiting and Improving The Students' Writing Scontrasting
confidence: 99%
“…The findings of this research showed that 50% respondents acquired fair score, and 17% was in poor qualification for their English writing. This finding was different from a study conducted by Toba, Noor, & Sanu (2019) who found that the English writing ability of undergraduate students can be considered as good. In addition, the results of this study was also not in line with Husin & Nurbayani's study (2017) who explained that the average score of thesis written in English by university students were relatively good quality.…”
Section: The Factors Inhibiting and Improving The Students' Writing Scontrasting
confidence: 99%
“…As stated by Setyowati (2016: 79-80), writing is a skill that difficult to master since there are many elements that must be considered by the writer to be able to produce a piece of a good writing, namely clear purpose, organization, word choice, language use, and ideas. However, Writing is one of the productive English skills that should be masterly skilled by English as Foreign Language (EFL) students in Indonesia for both written communication and academic writing purposes, such as; letters, essays, papers, articles, journals, project reports, theses, etc (Toba, Noor, & Sanu, 2019).…”
Section: Literature Review 21 Essay Writingmentioning
confidence: 99%
“…Another fact is that exposure to the facility to develop students' writing skills is still far from being sufficient. These problems are also listed by Toba et al (2019) as the main obstacles that most Indonesians face in their writing class.…”
Section: Introductionmentioning
confidence: 99%